2017
DOI: 10.1038/srep39959
|View full text |Cite
|
Sign up to set email alerts
|

Deformation mechanisms to ameliorate the mechanical properties of novel TRIP/TWIP Co-Cr-Mo-(Cu) ultrafine eutectic alloys

Abstract: In the present study, the microstructural evolution and the modulation of the mechanical properties have been investigated for a Co-Cr-Mo (CCM) ternary eutectic alloy by addition of a small amount of copper (0.5 and 1 at.%). The microstructural observations reveal a distinct dissimilarity in the eutectic structure such as a broken lamellar structure and a well-aligned lamellar structure and an increasing volume fraction of Co lamellae as increasing amount of copper addition. This microstructural evolution lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The hardness of the unmodified C17200 Cu substrate increases rapidly with the growth of the indentation depth and then gradually decreases after it reaches 5 GPa, until it keeps constant at 2.3 GPa during the unloading process. The increase in hardness in the early stage is caused by the size effect and the work-hardening effect [21][22][23][24]. Similarly, the modulus of the C17200 substrate turns to be about 150 GPa after a rapid growth.…”
Section: Resultsmentioning
confidence: 99%
“…The hardness of the unmodified C17200 Cu substrate increases rapidly with the growth of the indentation depth and then gradually decreases after it reaches 5 GPa, until it keeps constant at 2.3 GPa during the unloading process. The increase in hardness in the early stage is caused by the size effect and the work-hardening effect [21][22][23][24]. Similarly, the modulus of the C17200 substrate turns to be about 150 GPa after a rapid growth.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of brittle second phases helps to obtain an increase in shortening at a higher rate than does the load 26,27 , while plastic strain of Al alloys is enhanced influenced by the increased volume fraction of ductile α-Al solid solution and the lower amount of brittle intermetallic compounds 28 . In materials with hierarchical and/or complex microstructures there are reported both hardening and softening mechanisms, such as the works of Kim et al [28][29][30] , which revealed high work hardening rates at initial stages of plastic deformation. These rates gradually decreased at larger deformations, even obtaining negative values after the middle of plastic deformation, which indicates work softening behavior and the modification of the dominant deformation mechanism.…”
Section: Compressive Behaviormentioning
confidence: 99%
“…3a and Fig. 3b, respectively, where is obtained from Hollomon's equation: 26 (1) with denoting the flow stress and the strength coefficient. Even though is usually considered to be a constant, it is strain dependent in this case.…”
Section: Stress-strain Behaviormentioning
confidence: 99%